Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Facile oxidation of flavanones to flavones using [hydroxy(tosyloxy)iodo]benzene in an ionic liquid - Muthukrishnan, Murugan; Patil, P. S.; More, Shivaji V.; Joshi, Ramesh A. (Mendeleev Communications, 2005)
A method for the oxidation of flavationes to flavones has been developed using [hydroxy(tosyloxy)iodo] benzene (HTIB) in the room-temperature ionic liquid 1,3-di-n-butylimidazolium bromide ([bbim]Br-+(-)).

Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.

Concise synthesis of beta-blockers (S)-metoprolol and (S)-betaxolol using hydrolytic kinetic resolution - Muthukrishnan, Murugan; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A. (Tetrahedron, 2007)
Enantiopure (S)-metoprolol and (S)-betaxolol were prepared in an extremely simple and practical way using Jacobsen's hydrolytic kinetic resolution of terminal epoxides in isopropanol. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-blockers; betaxolol; Hydrolytic kinetic resolution; metoprolol

Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.

Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

Continuous-flow meerwein arylation - Bhaya, Vinay G.; Joshi, Ramesh A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2014)
The continuous-flow Meerwein arylation is demonstrated for a set of few aryl donors (anilines and m-aminoacetophenone) and specific radical acceptors. Homogeneous catalyst (CuBr in HBr and CuCl in HCl) was used to facilitate the reaction. The effect of parameters, viz., temperature, catalyst concentration, residence time, and concentration of the radical acceptor on the yield of the arylated product, was studied. The yield of the aryl derivative obtained by continuous-flow syntheses was always better than the respective experiments in batch mode. Flow synthesis allows easy variation in these parameters and thus allows going close to the maximum possible yields in a system where the relative rates of different reactions create a complex situation. Temperature plays a crucial role by affecting the rates as well as by governing the system homogeneity. The nitrogen bubbles generated in the reaction helped to avoid any channel blockage.
Keywords: diazonium salt; flow chemistry; homogeneous catalyst; Meerwein arylation; micromixer; multistep synthesis

Discontinuous two step flow synthesis of m-aminoacetophenone - Tibhe, Jagdish; Sharma, Yachita; Joshi, Ramesh A.; Joshi, Rohini R.; Kulkarni, Amol A. (Green Processing and Synthesis, 2014)
The continuous flow nitration of acetophenone followed by reduction of the meta isomer has been demonstrated using simple tubular reactors. Because of ease of separation of the desired isomer from the first step, both steps are made continuous, but separately. The continuous flow nitration was carried out in a safe manner in a shorter reaction time than the conventional approach. The choice of micromixer was seen to affect the performance of the nitration reaction. The effect of different parameters on the yield of the desired product was studied. The reduction step with sodium sulfide was found to be economical and could be carried out efficiently at 70 degrees C using sodium sulfide in ethanol, using a silicone tube. Both steps were demonstrated for several hours, yielding a sufficiently large quantity (similar to 100 g) of m-aminoacetophenone at lab scale in a single day using simple tubular reactors.
Keywords: acetophenone; continuous flow synthesis; microreactor; nitration; reduction

First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea

Continuous-flow nitration of o-xylene: effect of nitrating agent and feasibility of tubular reactors for scale-up - Sharma, Y.; Joshi, Ramesh A.; Kulkarni, A. A. (Organic Process Research & Development, 2015)
Continuous-flow nitration of o-xylene has been studied with different nitrating agents over a wide range of conditions for different parameters such as temperature, residence time, and concentrations. A nitrating mixture comprising sulfuric acid and fuming nitric acid was seen to yield higher selectivity for the isomer 1,2-dimethyl-3-nitrobenzene over the isomer 1,2-dimethyl-4-nitrobenzene and also a non-negligible quantity of dinitro derivatives of o-xylene. With only fuming nitric acid as the nitrating agent, the reaction was selective for 1,2-dimethyl-4-nitrobenzene over 1,2-dimethyl-3-nitrobenzene. Impurities mainly come from nitration of mononitro derivatives, and this occurs more from nitration of the 3-nitro isomer because of its higher reactivity with nitric acid. An economic analysis of the continuous-flow reactor for the production of 1,2-dimethyl-4-nitrobenzene at 100 and 500 kg/h in a jacketed tubular reactor showed that numbering-up is a more economical approach for higher production capacity. A combination of large- and small-sized tubes depending upon the relative rates of heat generation during a reaction will achieve more profit and a shorter payback period than having the entire reactor made of a single tube size.

First regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles - Rode, Navnath D.; Sonawane, Amol D.; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P. (Tetrahedron Letters, 2015)
The regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles is described for the first time. The iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles using molecular iodine afforded diiodo-compound which on Cul-catalyzed intramolecular C-N coupling reaction gave six-membered 2-aryl-51141,2,4]triazolo[5,1-b][1,3]thiazines, whereas, the five membered 3-aryl-5,6-dihydrothiazolo[2,3-c][1,2,4]triazoles were obtained exclusively when the iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles was carried out using NIS. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iodocyclization; Regloselective; Thiazine; Triazole

Regioselective and diastereoselective iodocyclization reaction of alkene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Sonawane, Amol D.; Auti, Jyoti B.; Rode, Navnath D.; Ranpise, Vinod R.; Joshi, Rohini R.; Joshi, Ramesh A. (New Journal of Chemistry, 2015)
Bicyclic beta-lactams, i.e. 3-thia-1-dethiacephams, were synthesized via a highly regioselective and diastereoselective iodocyclization reaction of alkene-thioureas with molecular iodine. Furthermore, the structure of 3-thia-1-dethiacepham was confirmed by a chemical method, the dehydrohalogenation reaction using DBU.

Synthesis of 3-Thia-1-dethiacephems via Regioselective Iodocyclization Reaction - Garud, Dinesh R.; Rode, Navnath D.; Bathe, Sagar R.; Ranpise, Vinod S.; Joshi, Ramesh A.; Joshi, Rohini R.; Koketsu, Mamoru (Synthesis-Stuttgart, 2015)
The key N-homopropargylthiourea intermediates, N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides, were prepared by the reaction of a 4-propargylazetidin-2-one with isothiocyanates. Bicyclic -lactams, i.e. 3-thia-1-dethiacephems, were prepared via highly regioselective iodocyclization reaction of N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides with molecular iodine at room temperature in moderate to excellent yields. A variety of functional groups were well tolerated under the reaction conditions.
Keywords: -lactams; 3-thia-1-dethiacephems; Iodocyclization; Regioselective; thiourea

Targeting dormant tuberculosis bacilli: results for molecules with a novel pyrimidone scaffold - Joshi, Rohit R.; Barchha, Avinash; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Sarkar, Sampa; Sarkar, Dhiman; Joshi, Rohini R.; Joshi, Ramesh A.; Shah, Anamik K.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2015)
Our inability to completely control TB has been due in part to the presence of dormant mycobacteria. This also renders drug regimens ineffective and is the prime cause of the appearance of drug-resistant strains. In continuation of our efforts to develop novel antitubercular agents that especially target dormant mycobacteria, a set of 55 new compounds belonging to the pyrimidone class were designed on the basis of CoMFA and CoMSIA studies, and these were synthesized and subsequently tested against both the dormant and virulent BCG strain of M.tuberculosis. Some novel compounds have been identified which selectively inhibit the dormant tuberculosis bacilli with significantly low IC50 values. This study reports the second molecule after TMC-207, having the ability to inhibit tuberculosis bacilli exclusively in its dormant phase. The synthesis was accomplished by a modified multicomponent Biginelli reaction. A classification model was generated using the binary QSAR approach - recursive partitioning (RP) to identify structural characteristics related to the activity. Physicochemical, structural, topological, connectivity indices, and E-state key descriptors were used for generation of the decision tree. The decision tree could provide insights into structure-activity relationships that will guide the design of more potent inhibitors.
Keywords: Antitubercular activity; dormant tuberculosis bacilli; pyrimidones; recursive partitioning

Continuous flow doebner–miller reaction and isolation using continuous stirred tank reactors - Yadav, Maruti B.; Kulkarni, Sourabh; Joshi, Ramesh A.; Kulkarni, Amol A. (Organic Process Research & Development, 2016)
Continuous flow Doebner–Miller synthesis of different quinaldines from respective anilines is demonstrated using sulfuric acid as a homogeneous catalyst. The extent of reaction was monitored for various parameters, namely, temperature, residence time, mole ratio of sulfuric acid to substrate, mole ratio of crotonaldehyde to substrate, and so forth. Continuous stirred reactors in series were used as a preferred configuration for this rection that generates byproduct in the form of sticky solid material. The approach has been extended for six different anilines, and the results are compared with batch reactions. Continuous stirred reactors in series with distributed dosing of crotonaldehyde facilitated a continuous flow reaction with lower byproduct formation, increased yields, and continuous workup and is a scalable approach.

Continuous flow telescopic oxidation of alcohols via generation of chlorine and hypochlorite - Sharma, Y.; Moolya, S.; Joshi, Ramesh A.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2017)
A 3-step continuous flow oxidation of alcohols is demonstrated with continuous generation of chlorine as the first step followed by its use for the flow synthesis of high strength sodium hypochlorite. The solution is subsequently used for oxidation of alcohols in the presence of a catalytic amount of the nitroxyl radical “TEMPO”, which inhibits oxidation at the aldehyde stage. Selective oxidations of eight different alcohols were demonstrated. To achieve identical yields, the aromatic alcohols containing electron withdrawing groups needed a longer residence time than aliphatic alcohols.

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis